Catalog of Templates - An Approach for Documenting Families of Hypermedia Documents - Santos, Rodrigo Costa Mesquita; Neto, Carlos de Salles Soares; Soares, Luiz Fernando Gomes (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
Two actors are identified in template-oriented authoring: the template author and the application author. Classifying hypermedia templates, aiming to support application authors in searching for suitable templates, in inferring on their semantic and in knowing how to fill them to generate applications is the focus of this paper. In doing so, it can be said that the proposed catalog somehow mediates the communication between template and application authors, favoring reuse and reducing the cognitive load; thereby facilitating application authoring. As an example of use, an indexing and storage apparatus, associated with a template authoring tool, and a search plug-in coupled with an application authoring tool are presented.